Impact of a Multidisciplinary Treatment Pathway for Atrial Fibrillation in the Emergency Department on Hospital Admissions and Length of Stay: Results of a Multi‐Center Study. Issue 18 (17th September 2019) - Ptaszek, Leon M.; Baugh, Christopher W.; Lubitz, Steven A.; Ruskin, Jeremy N.; Ha, Grace; Forsch, Margaux; DeOliveira, Samer A.; Baig, Samia; Heist, E. Kevin; Wasfy, Jason H.; Brown, David F.; Biddinger, Paul D.; et al.
Abstract : Background: Variability in the management of atrial fibrillation (AF) in the emergency department (ED) leads to avoidable hospital admissions and prolonged length of stay (LOS). In a retrospective single‐center study, a multidisciplinary AF treatment pathway was associated with a reduced hospital admission rate and reduced LOS. To assess the applicability of the AF pathway across institutions, we conducted a 2‐center study. Methods and Results: We performed a prospective, 2‐stage study at 2 tertiary care hospitals. During the first stage, AF patients in the ED received routine care. During the second stage, AF patients received care according to the AF pathway. The primary study outcome was hospital admission rate. Secondary outcomes included ED LOS and inpatient LOS. We enrolled 104 consecutive patients in each stage. Patients treated using the AF pathway were admitted to the hospital less frequently than patients who received routine care (15% versus 55%; P <0.001). For admitted patients, average hospital LOS was shorter in the AF pathway cohort than in the routine care cohort (64 versus 105 hours, respectively; P =0.01). There was no significant difference in the average ED LOS between AF pathway and routine care cohorts (14 versus 12 hours, respectively; P =0.32). Conclusions: In this prospective 2‐stage, 2‐center study, utilization of a multidisciplinary AF treatment pathway resulted in a 3.7‐fold reduction in admission rate and a 1.6‐fold reduction in average hospital LOS for admitted patients. Utilization of the AF pathway was not associated with a significant change in ED LOS.